The genetic basis for differences in leaf form between Arabidopsis thaliana and its wild relative Cardamine hirsuta. - Hay, A; Tsiantis, M (2006)
A key question in biology is how differences in gene function or regulation produce new morphologies during evolution. Here we investigate the genetic basis for differences in leaf form between two closely related plant species, Arabidopsis thaliana and Cardamine hirsuta. We report that in C. hirsuta, class I KNOTTED1-like homeobox (KNOX) proteins are required in the leaf to delay cellular differentiation and produce a dissected leaf form, in contrast to A. thaliana, in which KNOX exclusion from leaves results in a simple leaf form. These differences in KNOX expression arise through changes in the activity of upstream gene regulatory sequences. The function of ASYMMETRIC LEAVES1/ROUGHSHEATH2/PHANTASTICA (ARP) proteins to repress KNOX expression is conserved between the two species, but in C. hirsuta the ARP-KNOX regulatory module controls new developmental processes in the leaf. Thus, evolutionary tinkering with KNOX regulation, constrained by ARP function, may have produced diverse leaf forms by modulating growth and differentiation patterns in developing leaf primordia.